(untitled) (Progressive Agriculture, 2016)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from December 2013 to May 2014 to evaluate the integrated use of poultry manure with prilled urea and USG for improving the growth, yield and protein content of aromatic Boro rice (cv. BRRI dhan50). The experiment was laid out in a randomized complete block design with three replications. The experiment comprised 14 treatments viz. control (no manure and no fertilizer), recommended dose of prilled urea (115 kg N ha-1), urea super granules (USG) 1.8 g (55 kg N ha-1), USG 2.7 g (80 kg N ha-1), poultry manure (PM) 2.5 t ha-1, PM 5 t ha-1, recommended dose of prilled urea + PM 2.5t ha-1, recommended dose of prilled urea + PM 5 t ha-1, 50% of recommended dose of prilled urea + PM 2.5 t ha-1, 50% of recommended dose of prilled urea + PM 5 t ha-1, USG 1.8 g + PM 2.5 t ha-1, USG 1.8 g + PM 5 t ha-1, USG 2.7 g + PM 2.5 t ha-1and USG 2.7 g + PM 5 t ha-1. The experiment was laid out in a randomized complete block design with three replications. Morphological characteristics, yield contributing characters and yield of aromatic Boro rice (cv. BRRI dhan50) were significantly influenced by integrated use of poultry manure with prilled urea and USG. USG 2.7 g + PM 5 t ha-1 gave the highest plant height, number of tillers hill-1 and total dry matter production at all sampling dates while their corresponding lowest values were recorded in control. The highest yield contributing characters viz. number of effective tillers hill-1 (13.08), grains panicle-1 (124.26g) and 1000-grain weight (21.41g) were recorded in USG 2.7 g + PM 5 t ha-1 and the lowest values were recorded in control. The highest grain yield (5.33 t ha-1) and protein content (7.49%) were obtained at USG 2.7 g + PM 5 t ha-1 which was as good as recommended dose of prilled urea (115 kg N ha-1) + PM 5 t ha-1, USG 2.7 g + PM 2.5 t ha-1, USG 1.8 g + PM 5 t ha-1, recommended dose of prilled urea (115 kg N ha-1) + PM 2.5 t ha-1 while the lowest one (2.00 t ha-1) was obtained in control plots. The integrated use of poultry manure (5 t ha-1) with USG 1.8 g (55 kg N ha-1) appeared as the promising practice because of reducing considerable amount of prilled urea or USG in aromatic Boro rice (cv. BRRI dhan50) cultivation in terms of grain yield and grain protein content. Progressive Agriculture 27 (2): 86-93, 2016